Beautiful question : finding nature's deep design - Wilczek, Frank (New York: Penguin Books, 2016)
Does the universe embody beautiful ideas? Artists as well as scientists throughout human history have pondered this "beautiful question." With Nobel laureate Frank Wilczek as your guide, embark on a voyage of related discoveries, from Plato and Pythagoras up to the present. Wilczek's groundbreaking work in quantum physics was inspired by his intuition to look for a deeper order of beauty in nature. In fact, every major advance in his career came from this intuition: to assume that the universe embodies beautiful forms, forms whose hallmarks are symmetry--harmony, balance, proportion--and economy. There are other meanings of "beauty," but this is the deep logic of the universe--and it is no accident that it is also at the heart of what we find aesthetically pleasing and inspiring. As he reveals here, this has been the heart of scientific pursuit from Pythagoras, the ancient Greek who was the first to argue that "all things are number," to Galileo, Newton, Maxwell, Einstein, and into the deep waters of twentieth-century physics. Gorgeously illustrated, A Beautiful Question is a mind-shifting book that braids the age-old quest for beauty and the age-old quest for truth into a thrilling synthesis. Yes: the world is a work of art, and its deepest truths are ones we already feel, as if they were somehow written in our souls.--From publisher description.
Includes bibliographical references (pages 407-409) and index.
Keywords: Physics -- Philosophy; Science -- Aesthetics; Harmony of the spheres